„Doing Good” in Inhospitable World – According to St Peter’s First Epistle - Kiersztejn, Joanna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
This article gives a short analysis of a greek word agathopoieō as “doing good” in a perspective of First Epistle of Peter. The Author of the letter shows the importance of “doing good” in a hostile society. Christians as members of a Roman society were often treated as “not citizens” (paroikos) with a resentment and disgust. Despite the fact they were often victims of verbal and physical violence they could become the witnesses of the faith by “doing good”. Surprisingly agathopoieō can become an element of a dialog in an antagonistic world.